2002
DOI: 10.1002/acp.845
|View full text |Cite
|
Sign up to set email alerts
|

Children's reports of emotionally laden events: adapting the interview to the child

Abstract: This study examined the influence of expressive vocabulary and temperament on children's verbal reports about emotionally laden events in different interview conditions. In one of three conditions, 58 children aged between 5 and 7 years were interviewed about a time they had felt happy and a time they had felt scared. The interview conditions were: drawing, in which they were asked to draw and tell; re-enactment, in which they were asked to re-enact and tell; and verbal, in which they were simply asked to tell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
52
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 25 publications
4
52
1
Order By: Relevance
“…The present data add to a growing body of research showing that, under some circumstances, drawing facilitates children's verbal reports when they are interviewed about a wide range of past experiences (Drucker et al, 1997;Butler et al, 1995;Gross & Hayne, 1998, 1999Patterson & Hayne, 2007;Salmon et al, 2003;Wesson & Salmon, 2001). Consistent with prior research, children given the opportunity to draw reported more information than children only asked to tell.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The present data add to a growing body of research showing that, under some circumstances, drawing facilitates children's verbal reports when they are interviewed about a wide range of past experiences (Drucker et al, 1997;Butler et al, 1995;Gross & Hayne, 1998, 1999Patterson & Hayne, 2007;Salmon et al, 2003;Wesson & Salmon, 2001). Consistent with prior research, children given the opportunity to draw reported more information than children only asked to tell.…”
Section: Discussionsupporting
confidence: 84%
“…Although drawing does not always facilitate children's reports (Butler et al, 1995: Experiment 2;Salmon & Pipe, 2000), numerous studies have now shown that it can be effective when used with children who range in age from 3 to 12 years old (Drucker, Greco-Vigorito, Moore-Russell, Avaltroni, & Ryan, 1997;Gross & Hayne, 1998;Patterson & Hayne, 2007;Salmon, Roncolato, & Gleitzman, 2003;Wesson & Salmon, 2001). Furthermore, in the two studies in which it was assessed, drawing did not have a negative effect on accuracy (Gross & Hayne, 1998;Patterson & Hayne, 2007).…”
mentioning
confidence: 99%
“…In other words, the effect of language ability on recall may be more pervasive for younger children, constraining their encoding and subsequent retrieval of verbal information. By age 5 or 6, it may be children's ability to express rather than comprehend information that is more influential (see Salmon, Roncolato, & Gleitzman, 2003). Although findings have been mixed (e.g., Brown & Pipe, 2003;Gordon et al, 1993;Greenhoot, Ornstein, Gordon, & Baker-Ward, 1999), other studies have also highlighted the association between language ability and verbal recall (e.g., Boland et al, 2003; Burgwyn-Bailes, Baker-Ward, Gordon, & Ornstein, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Emotional language was defined as any utterance related to emotions, including explicit emotion labels, words identifying emotional facial displays (e.g., cry, laugh, smile), and words reflecting desires and preferences (e.g., like, love, hate, want; Salmon, Roncolato, & Gleitzman, 2003). Explicit emotion labels included references to people (I was happy), things (It was a happy movie) or events (It was sad when he left) and phrases that included the word feel .…”
Section: Methodsmentioning
confidence: 99%